What is missing in metacognitive instruction: A closer look at Indonesian English Education Research - Maman Asrobi; Nunung Suryati; Francisca Maria Ivone; Niamika El Khoiri (Universitas Syiah Kuala, 2025)
This systematic review examined the application of metacognitive strategies in English language education in Indonesia, focusing on studies published over the past decade (2014-2024). Following Booth et al.s (2021) model, the review analyzed 50 articles selected from 36 SINTA-accredited journals at levels 1 through 4, each centered on English language teaching or language education. The analysis identified key trends in research design, participant demographics, language skills, data collection methods, and analytical techniques used within the field. Findings revealed a predominant focus on undergraduate learners, while junior high, senior high, and postgraduate students were studied far less frequently. Reading skills emerged as the most extensively explored area, whereas speaking, writing, vocabulary, and translation received comparatively limited attention. Additionally, the review highlighted a strong reliance on quantitative methodologies, particularly questionnaires and tests, with fewer qualitative approaches, including interviews and classroom observations, being utilized. Based on these findings, the review supports a broader range of methodological approaches and expanded research on underrepresented learner groups and language skills to capture a more holistic view of metacognitive strategy applications. Moreover, it emphasizes the potential benefits of longitudinal and qualitative studies in understanding the long-term impacts of metacognitive strategies. These findings provide valuable direction for educators and policymakers, suggesting improvements in research diversity and integrating emerging technologies to strengthen learners metacognitive development and support English language education in Indonesia.